Cities and climate change - ROTH, Matthias (Institutional Knowledge at Singapore Management University, 2025)
We are pleased to present this special virtual collection of articles, highlighting the multifaceted interactions between cities, local climates, and global anthropogenic climate change. Climate change and urbanisation are the two global megatrends that transform human life and, at the same time, directly impact each other. Urban areas have the highest density of human populations and experience altered atmospheric conditions due to anthropogenic modification of natural physical settings and extra emissions of air pollutants and trace gases. One of the most obvious examples of climate modification due to humans is the urban heat island (UHI). This phenomenon describes urban regions, which experience higher temperatures than their rural, undeveloped surroundings, particularly at night, serving as a clear example of localised urban climate change.